The hygienic standards of xenobiotics in different environments as a unified system - M. R. Gzhegotsky; B. M. Shtabsky; L. M. Shafran; W. Zukow (Journal of Education, Health and Sport, 2015)
Gzhegotsky M. R., Shtabsky B. M., Shafran L. M., Zukow W. The hygienic standards of xenobiotics in different environments as a unified system. Journal of Education, Health and Sport. 2015;5(1):31-40. ISSN 2391-8306. DOI: 10.13140/2.1.2725.1523